Construction of Household Accounting Practices: an Islamic Ethnomethodological Study - Thalib, Mohamad Anwar (IAIN Kudus, 2023)
This research departs from the problem of modern accounting knowledge, which is limited to material and ignores non-material values, and studies of household accounting based on non-material values, which are rarely disclosed in accounting studies. This study aims to construct household cost accounting based on non-material values. This study uses an Islamic paradigm with an Islamic ethnomethodological approach. The results of the study found that household expenses were recorded by the wives, both recorded on paper and in memory. The income earned by the husband is sufficient to finance household needs, saved to finance unexpected needs, and finance business capital. There are expenses for alms, but alms are not considered a burden but a means of purifying wealth and charitable savings in the afterlife. The three household cost accounting practices are based on the values of responsibility, cooperation, and faith in the Creator.